1997
DOI: 10.1136/mp.50.5.266
|View full text |Cite
|
Sign up to set email alerts
|

A rapid RT-PCR based method for the detection of BCR-ABL translocation.

Abstract: The suggested one step PCR strategy is a simple and reliable way to reveal BCR-ABL chimaeras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The lentiviral pHIV7-GFP vector containing the shRNA specific for the b3a2 (e14a2) translocation breakpoint of BCR/ABL was provided by J. Rossi (Beckman Research Institute, City of Hope, Duarte, California, USA). Prior to transduction, the presence of the b3a2 BCR-ABL1 translocation was assessed by RT-PCR, as previously described (57). pBAR and pfuBAR.…”
Section: Figurementioning
confidence: 99%
“…The lentiviral pHIV7-GFP vector containing the shRNA specific for the b3a2 (e14a2) translocation breakpoint of BCR/ABL was provided by J. Rossi (Beckman Research Institute, City of Hope, Duarte, California, USA). Prior to transduction, the presence of the b3a2 BCR-ABL1 translocation was assessed by RT-PCR, as previously described (57). pBAR and pfuBAR.…”
Section: Figurementioning
confidence: 99%
“…Guo et al have shown that the BCR-ABL gene is highly expressed in myelogenous leukemia cells [23]. In addition, Yu et al showed that real-time qRT-PCR was able to detect the mRNA produced by the BCR-ABL gene [24].…”
Section: Resultsmentioning
confidence: 99%
“…The first assays to screen cancer patients for somatic alterations targetable by drugs were based on detection of single gene alterations [8]. For example, early studies investigating the genomic landscapes of breast cancers identified HER2 copy number amplifications in ~30% of patients, noting that overexpression of HER2 was associated with poor prognosis [9].…”
mentioning
confidence: 99%